Practices and Factors of Self-Medication in Iraqi Adults: A Cross-Sectional Study - Mohammed, Zainab Sajid; Al-Kraity, Wijdan Rajh Hamza (Medical Science Journal for Advance Research, 2026)
Background: Self-medication, which can be defined as taking medicines without a professional prescription, is a common trend in all parts of the world, and can result in adverse drug reactions, development of drug resistance and subsequent delayed diagnosis. There is scanty information on self-medication in Iraq. Objective:To determine the prevalence, causes, awareness and aspects related to self-medication in the case of Iraqi adults. Methods: A survey was done on 150 adults with a structured questionnaire and distributed in the open spaces and in pharmacies of the communities. Information covered demographics, type of drugs used, motivation of self-medication, obtained information and knowledge of risk possibilities. Associations were tested using descriptive statistics and chi-square. Results: Self-medication was found to be prevalent (68). The most common types of drugs were pain killers (45 percent), antibiotics (30 percent) and cold/flu drugs (25 percent). Major (40 percent) and cost avoidance (35 percent) reasons were major. The knowledge about negative effects was moderate, and 55% of the respondents said they read drug leaflets. Sixty percent of the participants sought pharmacist advice. Conclusion: Iraqi adults have self-medication that is common. The role of community pharmacists is to be increased and made more aware to the population in order to practice safe medication.